2011
DOI: 10.1063/1.3627181
|View full text |Cite
|
Sign up to set email alerts
|

Ion current rectification in a fluidic bipolar nanochannel with smooth junction

Abstract: We have simulated bipolar nanochannel based fluidic diode for different values of junction sharpness. We can obtain significant ion current rectification even for a smooth junction between oppositely charged zones. The rectification increases with junction sharpness due to increase in unipolar character of electrolyte but a sharp junction is not a necessary condition for rectification. The ion current rectification increases with surface charge density due to increase in unipolar character of electrolyte and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Although bipolar nanopores have been studied with the PNP theory extensively [54,36,23,55,56,2,57,58,59,60,61,62,63,64], we are not aware of any paper where this system is examined by molecular simulations apart from our previous study for a rectifying bipolar ion channel [65] and our parallel study where we compare to PNP [66]. We are aware only of a few MD studies [67,68,69,70,71,72] for other types of nanopores.…”
Section: Questionsmentioning
confidence: 99%
“…Although bipolar nanopores have been studied with the PNP theory extensively [54,36,23,55,56,2,57,58,59,60,61,62,63,64], we are not aware of any paper where this system is examined by molecular simulations apart from our previous study for a rectifying bipolar ion channel [65] and our parallel study where we compare to PNP [66]. We are aware only of a few MD studies [67,68,69,70,71,72] for other types of nanopores.…”
Section: Questionsmentioning
confidence: 99%
“…However, this is not a prerequisite of CICP and even a relatively weak, nonideal permselectivity can give rise to it. This has been confirmed by numerous theoretical and experimental studies dealing with the CICP of micro/nanointerfaces, in particular, in the so‐called nanofluidic diodes . A considerable part of theoretical studies neglected volume transfer.…”
Section: Introductionmentioning
confidence: 78%
“…For macroscopically homogeneous nanoblocks (no explicit dependence of transport coefficients on the macroscopic coordinate, x), the integration over the space variable in Equation (23) can be replaced by the integration over the virtual salt concentration by using Equation (9). Besides, we substitute the expression for the effective salt flux of Equation (12). As a result, the problem is solved in quadratures, and reduced to this system of transcendental equations for the volume flux, j v , and interface concentration, c i .…”
Section: Theorymentioning
confidence: 99%
“…Moreover, Singh et al. 77 showed that the rectification effect in a bipolar channel increases with increasing junction sharpness due to an increasing unipolar characteristic of the electrolyte.…”
Section: Applicationsmentioning
confidence: 99%